2015
DOI: 10.1111/coep.12102
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated Effects of California's Paid Family Leave Program

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 18 publications
4
45
1
1
Order By: Relevance
“…For example, Stanczyk () found evidence that California's PFL program does not meaningfully reduce the risk of poverty or increase household income among low‐income single‐mother households in the period closely following a birth. Further suggesting that California's PFL program might have unintended consequences for less advantaged mothers, Das and Polachek () found evidence that the program influenced young women's labor market participation by increasing the likelihood and duration of unemployment spells among this group. Finally, scholars have also found that among women, being low‐income and less‐educated is negatively related to awareness of PFL programs, which may weaken the positive effects of PL on vulnerable, single‐mother families and raises concerns about how these families fare during the period around a birth (Applebaum & Milkman, 2013).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…For example, Stanczyk () found evidence that California's PFL program does not meaningfully reduce the risk of poverty or increase household income among low‐income single‐mother households in the period closely following a birth. Further suggesting that California's PFL program might have unintended consequences for less advantaged mothers, Das and Polachek () found evidence that the program influenced young women's labor market participation by increasing the likelihood and duration of unemployment spells among this group. Finally, scholars have also found that among women, being low‐income and less‐educated is negatively related to awareness of PFL programs, which may weaken the positive effects of PL on vulnerable, single‐mother families and raises concerns about how these families fare during the period around a birth (Applebaum & Milkman, 2013).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…12 Das and Polachek (2015) also consider the impact of family leave regulations on unemployment, but they study the impact on unemployment of all young women, not specifically that of mothers after childbirth.…”
mentioning
confidence: 99%
“…Both studies find that access to paid family leave increased leave-taking on the intensive margin, while Slater, Ruhm, and Waldfogel also find increased work hours and higher wages for mothers who had returned to work after giving birth. Focusing on the same California paid leave policy, Das and Polachek (2015) report that, compared to men and older women, younger women experienced an increase in labor force participation and unemployment following the mandate. Byker (2016) studies the California paid leave mandate and a similar policy adopted in New Jersey in 2009 and also finds evidence of increased labor force participation for women.…”
Section: Department Of Labor 2016)mentioning
confidence: 99%